Wound-Induced Regeneration in Feather Follicles: A Stepwise Strategy to Regenerate Stem Cells - Ting-Xin Jiang; Ping Wu; Ang Li; Randall B. Widelitz; Cheng-Ming Chuong (Journal of Developmental Biology)
How to elicit and harness regeneration is a major issue in wound healing. Skin injury in most amniotes leads to repair rather than regeneration, except in hair and feathers. Feather follicles are unique organs that undergo physiological cyclic renewal, supported by a dynamic stem cell niche. During normal feather cycling, growth-phase proximal follicle collar bulge stem cells adopt a ring configuration. At the resting and initiation phases, these stem cells descend to the dermal papilla to form papillary ectoderm and ascend to the proximal follicle in a new growth phase. Plucking resting-phase feathers accelerates papillary ectoderm cell activation. Plucking growth-phase feathers depletes collar bulge stem cells; however, a blastema reforms the collar bulge stem cells, expressing KRT15, LGR6, Sox9, integrin-α6, and tenascin C. Removing the follicle base and dermal papilla prevents feather regeneration. Yet, transplanting an exogenous dermal papilla to the follicle base can induce re-epithelialization from the lower follicle sheath, followed by feather regeneration. Thus, there is a stepwise regenerative strategy using stem cells located in the collar bulge, papillary ectoderm, and de-differentiated lower follicle sheath to generate new feathers after different levels of injuries. This adaptable regenerative mechanism is based on the hierarchy of stem cell regenerative capacity and underscores the remarkable resilience of feather follicle regenerative abilities.